Evaluation of Community Preparedness for Forest and Land Fire Management - Harjanti, Diah Trismi; Putri, Hafiziani Eka; Windusari, Firdha Anugrah; Arini, Audi Cindra; Fujianti, Lia Nurbanillah (Universitas Tanjungpura, 2024)
The village of Rasau Jaya Dua is primarily composed of peatlands, and since most of its residents are farmers, much of their agricultural activities take place on these lands. The practice of burning peatlands for farming purposes raises the risk of forest and land fires. Additionally, careless actions like burning waste or improperly discarding cigarette butts on peatlands can also trigger fires. For this reason, researchers must evaluate the community